2000
DOI: 10.1007/bf03032656
|View full text |Cite
|
Sign up to set email alerts
|

CRP, TNFα, IL-1ra, IL-6, IL-8 and IL-10 in blood serum of colorectal cancer patients

Abstract: Blood serum cytokines: TNFalpha, IL-1ra, IL-6, IL-8, IL-10 as well as CRP were investigated in patients with colorectal cancer, prior treatment and 1, 10 and 42 days after surgery. There was an increase of the levels of CRP, IL-6 and IL-10 in most patients 24 hours after surgery. The levels of IL-1ra were elevated in patients in stage C and in several patients in stage B of the disease and there was a decrease of circulating TNFalpha in stage B patients. On day 10 and 42 after surgery, the levels of cytokines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
3
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 9 publications
7
32
3
5
Order By: Relevance
“…In the sera of the patients with CRC, a significant elevation was also noted in the levels of the pro-inflammatory cytokines TNF-α, IL-6, and IL-8, consistent with the results earlier presented by other authors (Belluco et al 2000;Kamiñska et al 2000). Moreover, the levels of the cytokines in the patients with CRC and those with CD showed no significant differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the sera of the patients with CRC, a significant elevation was also noted in the levels of the pro-inflammatory cytokines TNF-α, IL-6, and IL-8, consistent with the results earlier presented by other authors (Belluco et al 2000;Kamiñska et al 2000). Moreover, the levels of the cytokines in the patients with CRC and those with CD showed no significant differences.…”
Section: Discussionsupporting
confidence: 91%
“…Already published data have presented contradictory results Table 1. Cytokine levels (TNF-α, IL-1β, IL-6, IL-8, IL-10) in sera of the healthy subjects and patients with UC, CD, or CRC related to preoperative serum IL-10 levels in CRC patients, pointing to a relationship between higher IL-10 levels and an inoperable tumor (Galizia et al 2002;Kamiñska et al 2000). On the other hand, our study was conducted in patients with operable CRC (Dukes' stage B), which may explain the contradictions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high expression of this marker in Dukes' C CRC Japanese patients was a favorable indicator of prognosis [3] . Another study reported that, among other cytokines, TNF was significantly elevated in stage B patients prior to surgery [30] .…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been postulated that proin fl amm ato ry cy to kin es st ron gl y i nf lu e nce t he immunological status of CRC [3] . Among them, IL-6 and TNF can initiate the innate immune response by inducing the acute phase of inflammation [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…В частности, IL-1β активирует продукцию IL-8, стимулирующего пролиферацию опухолевых клеток и участвующего в ангиогенезе, который, в конечном счете, обеспечивает инвазию опухоли и метастазирование [9]. IL-1ra, являющийся ре-цепторным антагонистом IL-1 и образующийся в ответ на повышенные уровни последнего, с од-ной стороны, может ограничивать его пролифе-ративные и ангиогенные эффекты, а с другой -может поддерживать воспаление на таком уровне, когда не происходит элиминации возникающих атипических клеток и создаются все предпосыл-ки для возникновения опухоли и ее дальнейшего прогрессирования [4,6].…”
Section: Introductionunclassified